Evaluation of the Endomysial Antibody for Celiac Disease: Operating Properties and Associated Cost Implications in Clinical Practice - Kenneth Atkinson; Sonya Tokmakajian; William Watson; James Gregor (Canadian Journal of Gastroenterology)
OBJECTIVE: To evaluate the operating properties of endomysial antibodies (EMAs) in the diagnosis of celiac disease and to examine, using a cost minimization model, different strategies used in the diagnosis of celiac disease.